Combined effects of Bacillus sp. M6 strain and Sedum alfredii on rhizosphere community and bioremediation of cadmium polluted soils - Abid, Abbas Ali; Zhang, Gengmiao; He, Dan; Wang, Huanhe; Batool, Itrat; Di, Hongjie; Zhang, Qichun (Frontiers in Plant Science, 2022)
Concerns regarding inevitable soil translocation and bioaccumulation of cadmium (Cd) in plants have been escalating in concomitance with the posed phytotoxicity and threat to human health. Exhibiting a Cd tolerance, Bacillus sp. M6 strain has been reported as a soil amendment owing to its capability of reducing metal bioavailability in soils. In present study, rhizospheric bacterial community of the Cd hyperaccumulator Sedum alfredii was investigated using 16S rRNA gene sequencing. Additionally, the Cd removal efficiency of strain Bacillus sp. M6 was enhanced by supplementing with biochar (C), glutamic acid (G), and rhamnolipid (R) to promote the phytoremediation effect of hyperaccumulator Sedum alfredii. To the best of our knowledge, this is the first time the amendments such as C, G and R together with plant-microbe system Sedum alfredii-Bacillus sp. M6 have been used for Cd bioremediation. The results showed that soil CaCl2 and DTPA (Diethylenetriamine penta-acetic acid) extractable Cd increased by 52.77% and 95.08%, respectively, in all M6 treatments compared to unamended control (CK). Sedum alfredii with Bacillus sp. M6 supplemented with biochar and rhamnolipid displayed a higher phytoremediatory effect and the removal capability of soil Cd (II) reached up to 16.47%. Moreover, remediation of Cd polluted soil by Bacillus sp. M6 also had an impact on soil microbiome, including ammonia-oxidizing bacteria (AOB), ammonia-oxidizing archaea (AOA) and cadmium transporting ATPase (cadA) genes. Quantitative PCR analysis confirmed the Bacillus sp. M6 strain increased the abundance of AOB and cadA in both low Cd (LC) and high Cd (HC) soils compared to AOA gene abundance. Besides, the abundance of Proteobacteria and Actinobacteria was found highest in both soils representing high tolerance capacity against Cd. While Firmicutes ranked third, indicating that the addition of strain couldn't make it the most dominant species. The results suggested the presence of the hyperaccumulator Sedum alfredii and Cd tolerant strain Bacillus sp. M6 supplemented with biochar, and rhamnolipid, play a unique and essential role in remediation process and reducing the bioavailability of Cd.